2011
DOI: 10.1371/journal.pone.0023005
|View full text |Cite
|
Sign up to set email alerts
|

Diversification and Molecular Evolution of ATOH8, a Gene Encoding a bHLH Transcription Factor

Abstract: ATOH8 is a bHLH domain transcription factor implicated in the development of the nervous system, kidney, pancreas, retina and muscle. In the present study, we collected sequence of ATOH8 orthologues from 18 vertebrate species and 24 invertebrate species. The reconstruction of ATOH8 phylogeny and sequence analysis showed that this gene underwent notable divergences during evolution. For those vertebrate species investigated, we analyzed the gene structure and regulatory elements of ATOH8. We found that the bHLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…In general, animal models rather than human subjects are used in development and gene-function studies owing to ethical issues. However, the species variation of ATOH8 might indicate that it has different functions in different cellular contexts, especially for Hath6, as previously suggested (Chen et al, 2011). The findings from hESC and EC studies emphasized the significance of Hath6 in the control of endothelial-specific gene expression, cell-fate determination and possibly the genetic program that permits mechanotransduction.…”
Section: Discussionmentioning
confidence: 74%
“…In general, animal models rather than human subjects are used in development and gene-function studies owing to ethical issues. However, the species variation of ATOH8 might indicate that it has different functions in different cellular contexts, especially for Hath6, as previously suggested (Chen et al, 2011). The findings from hESC and EC studies emphasized the significance of Hath6 in the control of endothelial-specific gene expression, cell-fate determination and possibly the genetic program that permits mechanotransduction.…”
Section: Discussionmentioning
confidence: 74%
“…To some extent, this result demonstrated that the signature could explain the nature of the Fuhrman grading system based upon nuclear size, and the shape and prominence of nucleoli . ATOH8 is recognized as a transcriptional factor that has important roles in cell differentiation and developmental biology . ATP1A3 and CNGA1 are important in cellular energy metabolism, while CHMP4C belongs to the chromatin‐modifying protein family and is associated with nucleus organization .…”
Section: Discussionmentioning
confidence: 99%
“…For example only four bHLH genes and their orthologs (Ascl1, Atoh1/7, Neurog1/2 and Neurod1) are necessary for the development of ∼90% of the neurons in the mammalian brain [cerebellum, cochlear nuclei, large areas of the cortex and sensory cells and neurons of the eye and ear (Bermingham, et al, 2001, Pan, et al, 2009)] and all sensory neurons bringing information into the brain. Indeed, most of the group A bHLH genes are associated with neurosensory development (Chen, et al, 2011, Imayoshi and Kageyama, 2014) and seem to be linked to the evolution of neurons (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%